Lithium-rich manganese-based positive electrode material and preparation method thereof

By using nickel-cobalt lithium manganate core coated with layered/spinel composite phase transition layer and lithium zirconium phosphate layer in the positive electrode material of lithium ion battery, the problems of low specific capacity and poor structural stability of lithium ion battery are solved. Higher energy density and cycling performance are achieved.

CN119170770APending Publication Date: 2024-12-20NINGBO UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411315522.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have low specific capacity, poor structural stability and compatibility with electrolytes limit their application in high-performance lithium-ion batteries.

Method used

The lithium-rich manganese-based positive electrode material is coated with a layered/spinel composite phase transition layer and a lithium zirconium phosphate layer, and absorbs lithium ion deintercalation stress through the layered/spinel composite phase transition layer. Improve mechanical strength and lithium ion diffusion efficiency, and improve surface oxygen saturation and structural stability through lithium zirconium phosphate layer.

Benefits of technology

It significantly improves the specific capacity, cycling stability and high voltage tolerance of the material, suppresses voltage attenuation and capacity attenuation, and improves the energy density and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170770A_ABST
    Figure CN119170770A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-rich manganese-based positive electrode material, which comprises a nickel cobalt lithium manganate core, a layered / spinel composite phase transition layer coated on the surface of the core, and a lithium zirconium phosphate layer coated on the surface of the layered / spinel composite phase transition layer. The layered / spinel composite phase transition layer and the lithium zirconium phosphate layer in the lithium-rich manganese-based positive electrode material can stabilize a lithium ion transmission channel in nickel cobalt lithium manganate in a cycle process, inhibit structure degradation caused by lattice oxygen evolution, inhibit voltage decline and improve cycle stability. The invention further discloses a preparation method of the lithium-rich manganese-based positive electrode material, through a low-temperature rapid melting method, the lithium zirconium phosphate layer can permeate into particles along the grain boundary of the nickel cobalt lithium manganate particles in the melting reaction process, and a surface-grain boundary integrated coating layer is formed. The invention also discloses a lithium ion battery which comprises a positive pole piece, a negative pole piece, a diaphragm and an electrolyte, and the positive pole piece comprises the lithium-rich manganese-based positive pole material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] With the development of the times, the industrial application of lithium-ion batteries is advancing rapidly. In the fields of new energy electric vehicles, grid energy storage, and portable mobile devices, in addition to the current low-carbon, safe, environmentally friendly, and long cycle life, the improvement of its energy density has always been the focus of people's attention. Lithium-ion batteries are widely used in the field of electric vehicles because of their high operating voltage, high energy density and power density, and long cycle life. In lithium-ion batteries, the positive electrode material accounts for the highest proportion of the battery, about 40%, which directly affects the energy density, safety, and cycle stability of the battery. At present, the commercial lithium-ion battery positive electrode materials include LiCoO2, LiMn2O4, and LiFePO4, and the specific capacity is less than 200mAh / g, which has become the main bottleneck restricting the improvement of the specific energy of lithium-ion batteries. Therefore, the development of high specific capacity positive electrode materials is an effective way to solve this problem.

[0003] Lithium-rich manganese-based cathode materials have become a hot topic of research due to their high specific capacity (>250mAh / g), low cost and good environmental friendliness. They are one of the important development directions of the next generation of power battery cathode materials. x Co y Mn 1-x-y O or xLi2MnO3·(1-x)LiTMO2 (TM=Mn, Ni, Co and other transition metal elements). This type of material usually has a layered structure and can store and release charges through the intercalation and deintercalation of lithium ions. Compared with traditional lithium-ion battery positive electrode materials, lithium-rich manganese-based positive electrode materials can participate in charge compensation at high voltages, thereby providing higher specific capacity and thus improving battery energy density.

[0004] However, lithium-rich manganese-based cathode materials also face some challenges in practical applications, such as structural stability during high-voltage charging and discharging, voltage attenuation during the cycle, and compatibility issues with the electrolyte. The existence of these problems limits its application in high-performance lithium-ion batteries. In order to overcome these problems, researchers have carried out a lot of research work, including improving the structural stability and electrochemical properties of materials through doping, surface modification, structural design and other means. In addition, the optimization of the electrolyte system is also considered to be an effective way to improve the performance of lithium-rich manganese-based cathode materials. However, there is still room for improvement in all of the above improvements. Summary of the invention

[0005] The purpose of the present application is to overcome the deficiencies of the above-mentioned prior art and to provide a lithium-rich manganese-based positive electrode material and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the technical solution adopted in the present application is: a lithium-rich manganese-based positive electrode material, comprising a lithium nickel cobalt manganese oxide core, a layered / spinel composite phase transition layer coated on the surface of the core, and a lithium zirconium phosphate layer coated on the surface of the layered / spinel composite phase transition layer;

[0007] The chemical formula of the lithium nickel cobalt manganese oxide core is shown in formula (I):

[0008] aLi2MnO3·(1-a)LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2(I);

[0009] Wherein, 0.4<a<0.6 (for example, a may be 0.45, 0.47, 0.49, 0.51, 0.53, 0.55, 0.57, but is not limited to the above values);

[0010] The chemical formula of the lithium zirconium phosphate is shown in formula (II):

[0011] LiZr2(PO4)3(II);

[0012] The chemical formula of the layered / spinel composite phase transition layer is shown in formula (III):

[0013] aLi2MnO3·(1-a)LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2·LiMn2O4(III).

[0014] The lithium-rich manganese-based positive electrode material described in the present invention is lithium nickel cobalt manganese oxide whose surface is sequentially coated with a layered / spinel composite phase transition layer and a lithium zirconium phosphate layer. The layered / spinel composite phase transition layer can absorb the stress of the lithium nickel cobalt manganese oxide layer structure during the lithium deintercalation process, thereby improving the mechanical strength of the material. At the same time, the spinel structure in the layered / spinel composite phase has a three-dimensional lithium ion channel, which can improve the lithium ion diffusion efficiency and improve the specific capacity characteristics of the material. The lithium zirconium phosphate layer has a high degree of oxygen saturation on the surface and a strong high voltage tolerance, which can improve the stability of the surface oxygen structure of the lithium nickel cobalt manganese oxide and inhibit the dissolution of the bulk Mn element, thereby improving the cycle performance of the material.

[0015] The lithium nickel cobalt manganese oxide core is a quasi-spherical particle with an average particle size of 5 to 100 μm, the thickness of the transition layer is 0.5 to 5.0 nm, and the thickness of the lithium zirconium phosphate layer is 0.1 to 2.0 nm. The average particle size of the lithium nickel cobalt manganese oxide core can be obtained by statistically testing with a scanning electron microscope, and the average value is taken after testing the particle sizes of 20 particles. The thickness of the transition layer and the lithium zirconium phosphate layer is obtained by testing with a transmission electron microscope (TEM).

[0016] Preferably, the nickel cobalt manganese oxide lithium core is a spherical particle with an average particle size of 5-100 μm (such as 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, but not The thickness of the transition layer is 0.5-4.0 nm (such as 0.5 nm, 1.0 nm, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, but not limited thereto), and the thickness of the lithium zirconium phosphate layer is 0.1-2.0 nm (such as 0.1 nm, 0.5 nm, 0.7 nm, 1.0 nm, 1.5 nm, 2.0 nm, but not limited thereto). More preferably, the average particle size of the lithium nickel manganese cobalt oxide is 5-50 μm, the thickness of the transition layer is 0.5-5.0 nm, and the thickness of the lithium zirconium phosphate layer is 0.1-2.0 nm.

[0017] The lithium nickel cobalt manganese oxide can be purchased from the market or prepared by conventional methods, such as the method mentioned in Jun Wang, Xiayin Yao, Xufeng Zhou and Zhaoping Liu*Synthesis and electrochemical properties of layered lithium transition metal oxides[J]J.Mater.Chem., 2011, 21, 2544-2549.

[0018] Preferably, relative to the weight of the lithium nickel cobalt manganese oxide core, the weight percentage of the lithium zirconium phosphate is 0.5-5% (such as 0.5%, 0.8%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, but not limited to these), preferably 0.5-3%, and more preferably 0.5-2%.

[0019] The present invention also provides a method for preparing the above-mentioned lithium-rich manganese-based positive electrode material, comprising the following steps:

[0020] S1. Obtaining lithium nickel cobalt manganese oxide particles;

[0021] S2. The lithium nickel cobalt manganese oxide particles, lithium source, zirconium source, phosphorus source and flux are uniformly mixed, sintered at 300-500°C for 0.5-2h, and then cooled to room temperature, and the product is washed, filtered, and the residue is dried;

[0022] S3. Annealing the dried filter residue to obtain the lithium-rich manganese-based positive electrode material.

[0023] The present invention preferably adopts a rapid melting method to sinter nickel cobalt manganese oxide lithium and a mixture of a phosphorus source and a zirconium source. During the calcination process, the P and Zr elements will penetrate into the grain boundaries, enter the bulk phase, and change the bulk phase structure. The oxygen saturation in the phosphate ions is high, which can inhibit the precipitation of oxygen under high voltage, improve the structural stability of the material, and thus inhibit the voltage decay and capacity decay during the high voltage long cycle process. The present invention uses a low-temperature rapid melting method, and during the melting reaction process, the lithium zirconium phosphate layer will penetrate into the particles along the grain boundaries of the nickel cobalt manganese oxide lithium particles to form a surface-grain boundary integrated coating layer. The process production stability is strong and can be applied to the mass production of materials.

[0024] Preferably, in S2, the mixing is: uniformly mixing the lithium nickel cobalt manganese oxide particles, lithium source, zirconium source, phosphorus source and flux in a solvent, and removing the solvent; preferably, in S2, the mixing is: uniformly mixing the lithium source, zirconium source and phosphorus source in an organic solvent to obtain slurry I, mixing the flux in water to a paste to obtain slurry II, uniformly mixing the lithium nickel cobalt manganese oxide particles, slurry I and slurry II, and drying to remove the organic solvent and water; more preferably, the organic solvent is a mixture of one or more of alcohols, aromatic hydrocarbons, ethers and ketones. Preferably, in S2, the sintering atmosphere is an air atmosphere, and the heating rate is 5°C / min.

[0025] Preferably, the amount of the lithium source, zirconium source and phosphorus source added is: 0.5-5wt% of the lithium zirconium phosphate generated by the total reaction of the lithium source, zirconium source and phosphorus source relative to the lithium nickel cobalt manganese oxide particles.

[0026] Preferably, in S3, the annealing treatment is carried out at a temperature of 180-250°C, preferably 180-220°C, and for a time of 45-120 min, preferably 45-90 min.

[0027] Preferably, the lithium source is at least one of lithium hydroxide, lithium nitrate, lithium sulfate, lithium chloride, lithium oxalate, lithium phosphate, lithium hydrogen phosphate and lithium carbonate; the zirconium source is at least one of zirconium nitrate, zirconium sulfate, zirconium chloride and hydrates thereof; the phosphorus source is at least one of (NH4)2HPO4, NH4H2PO4, lithium phosphate and lithium dihydrogen phosphate; the flux is at least one of LiCl, KCl, NaCl and CaCl2.

[0028] Preferably, the flux includes a first flux and a second flux; the first flux is at least one of LiCl and NaCl; the second flux is at least one of KCl and CaCl2; preferably, the flux is a mixture of LiCl and KCl; more preferably, the eutectic temperature of LiCl and KCl after mixing in proportion is 353°C.

[0029] The present invention also aims to provide a lithium-ion battery comprising: a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the lithium-rich manganese-based positive electrode material as described above, or the lithium-rich manganese-based positive electrode material prepared by the method as described above.

[0030] Compared with the prior art, the present invention has the following beneficial effects: the lithium-rich manganese-based positive electrode material described in the present invention is a lithium nickel cobalt manganese oxide whose surface is sequentially coated with a layered / spinel composite phase transition layer and a lithium zirconium phosphate layer; the layered / spinel composite phase transition layer and the lithium zirconium phosphate layer can stabilize the lithium ion transmission channel in the lithium nickel cobalt manganese oxide during the cycle, inhibit structural degradation caused by lattice oxygen precipitation, inhibit voltage decay and improve cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The scanning electron microscope (SEM) image and energy dispersive spectroscopy (EDS) surface scanning component distribution map of the lithium-rich manganese-based positive electrode material described in Example 1 are shown.

[0032] Figure 2 Raman spectra of Example 1 (LLO@LZP) and Comparative Example (LLO).

[0033] Figure 3 X-ray photoelectron spectroscopy (XPS) graphs of the lithium-rich manganese-based positive electrode materials described in Example 1 (LLO@LZP) and Comparative Example (LLO).

[0034] Figure 4 This is the XPS etching analysis diagram of the lithium-rich manganese-based positive electrode material described in Example 1.

[0035] Figure 5 (a) is a TEM image of the lithium-rich manganese-based positive electrode material described in Example 1 before charge and discharge cycles, Figure 5 (b) is a TEM image of the lithium-rich manganese-based positive electrode material described in Example 1 after charge and discharge cycles.

[0036] Figure 6 The first charge and discharge curves and specific capacity-cycle number diagrams of Example 1, Example 2, Example 5 and the comparative example are (a) for the comparative example, (b) for Example 1, (c) for Example 5 and (d) for Example 2.

[0037] Figure 7The graph of the median voltage of Example 1 and the comparative example during the cycle process varies with the number of cycles. DETAILED DESCRIPTION

[0038] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0039] In the following examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0040] Example 1

[0041] The lithium-rich manganese-based positive electrode material described in the present invention comprises a nickel-cobalt-manganese-oxide lithium core, a layered / spinel composite phase transition layer coated on the surface of the core, and a lithium zirconium phosphate layer (LiZr2(PO4)3) coated on the surface of the layered / spinel composite phase transition layer; the nickel-cobalt-manganese-oxide lithium core used in this embodiment is Li 1.2 Mn 0.53 Ni 0.13 Co 0.13 O2, purchased from CLUOD, with an average particle size of 10 μm, denoted as LLO@LZP or LLO@LZP 1%.

[0042] The preparation method of the lithium-rich manganese-based positive electrode material described in this embodiment comprises the following steps:

[0043] S1. Obtaining lithium nickel cobalt manganese oxide particles;

[0044] S2. The lithium nickel cobalt manganese oxide particles, lithium source, zirconium source, phosphorus source and flux are mixed evenly, sintered at 400° C. for 1 hour and then cooled to room temperature, and the product is washed, filtered and the residue is dried, specifically:

[0045] (1) Weighing raw materials for preparing lithium zirconium phosphate according to the addition amount of lithium zirconium phosphate generated by the complete reaction of lithium source, zirconium source and phosphorus source relative to 1 wt% of nickel cobalt manganese oxide particles, adding 0.145 parts by weight of LiNO3, 1.431 parts by weight of Zr(NO3)4·5H2O and 0.835 parts by weight of (NH4)2HPO4 to industrial alcohol (95%), grinding with a mortar to obtain slurry I; adding ultrapure water according to a ratio of 9 parts by weight of LiCl and 11 parts by weight of KCl, mixing and stirring until viscous, to obtain slurry II; adding slurries I and II and 100 parts by weight of nickel cobalt manganese oxide particles to industrial alcohol and grinding evenly, and drying at 60°C;

[0046] (2) Place the sintered product in a muffle furnace at 400°C, keep the temperature for 1 hour, and then air-cool it to room temperature;

[0047] (3) Filter three times with deionized water and pour a small amount of AgNO3 into the filtered water to observe whether there is a white precipitate. If not, it means that the AgCl precipitation in the filtered water has been reduced to the minimum, that is, the free Cl is reduced as much as possible. - , dried at 80°C for 12h;

[0048] S3. Annealing the dried filter residue at 200° C. for 1 h to obtain the lithium-rich manganese-based positive electrode material.

[0049] Figure 1 The SEM image and EDS surface scanning component distribution diagram of the lithium-rich manganese-based positive electrode material described in Example 1. It can be seen from the figure that phosphorus and zirconium elements are evenly distributed in the material, the surface coating layer has a high uniformity, and no obvious segregation occurs.

[0050] Figure 2 The Raman spectra of Example 1 (LLO@LZP) and Comparative Example (LLO) show that the modified LLO@LZP sample has a Raman peak at 650 cm -1 An obvious peak appeared at , indicating the formation of spinel phase (space group Fd-3m).

[0051] Figure 3 The XPS graphs of the lithium-rich manganese-based positive electrode materials described in Example 1 (LLO@LZP) and the comparative example (LLO) show that the valence state of Mn changes significantly, while Ni 2+ and Ni 3+ Ratio and Co 2+ and Co 3+ The proportion does not change significantly, Mn 3+ The proportion increased from 16% to 34%. 3+ The increase in element content indicates that the material forms spinel phase LiMn2O4 after coating.

[0052] Figure 4 This is the XPS etching analysis diagram of the lithium-rich manganese-based positive electrode material described in Example 1. As the etching depth increases, the concentrations of P and Zr elements do not change significantly, indicating that lithium zirconium phosphate not only coats the surface of the material, but also penetrates into the grain boundary gaps of the material, achieving full coating of the primary particles.

[0053] Figure 5 (a) is a TEM image of the lithium-rich manganese-based positive electrode material described in Example 1 before charge and discharge cycles, Figure 5 (b) is a TEM image of the lithium-rich manganese-based positive electrode material after charge and discharge cycles described in Example 1. Figure 5 (a) It can be seen that the thickness of the layered / spinel composite phase transition layer is about 1-3.5nm, and the thickness of the surface lithium zirconium phosphate layer is about 0.5-0.9nm. Figure 5(b) It can be seen that after the charge and discharge cycle, the surface structure of the lithium zirconium phosphate layer of the material is basically unchanged, the sub-outer layer transforms from the layered / spinel composite phase before the cycle to the spinel phase, while the bulk layered structure remains intact, indicating that the surface structure of the material has good stability.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that the sintering temperature in S2 is different. The sintering temperature in this embodiment is 500°C.

[0056] Example 3

[0057] The difference between this embodiment and embodiment 1 is that the amount of raw materials added for preparing lithium zirconium phosphate in S2 is different. In this embodiment, the raw materials for preparing lithium zirconium phosphate are weighed in an amount of 0.5 wt % of the lithium zirconium phosphate generated by the complete reaction of the lithium source, zirconium source and phosphorus source relative to the lithium nickel cobalt manganese oxide particles.

[0058] Example 4

[0059] The difference between this embodiment and embodiment 1 is that the amount of raw materials added for preparing lithium zirconium phosphate in S2 is different. In this embodiment, the raw materials for preparing lithium zirconium phosphate are weighed according to the addition amount of 2 wt % of lithium zirconium phosphate generated by the complete reaction of lithium source, zirconium source and phosphorus source relative to the lithium nickel cobalt manganese oxide particles.

[0060] Example 5

[0061] The difference between this embodiment and embodiment 1 is that the amount of raw materials added for preparing lithium zirconium phosphate in S2 is different. The raw materials for preparing lithium zirconium phosphate are weighed according to the addition amount of 3wt% of lithium zirconium phosphate generated by the complete reaction of lithium source, zirconium source and phosphorus source relative to the lithium nickel cobalt manganese oxide particles.

[0062] Comparative Example

[0063] This comparative example is the lithium nickel manganese oxide particles Li in Example 1 1.2 Mn 0.53 Ni 0.13 Co 0.13 O2, denoted as LLO.

[0064] Effect example

[0065] Using N-methylpyrrolidone (NMP) as solvent, mix the materials in the examples and comparative examples with polyvinylidene fluoride, conductive carbon black, and conductive carbon nanofibers in a mass ratio of 90:5:2.5:2.5 and apply them on aluminum foil to make a positive electrode. Then use the lithium sheet as the negative electrode to assemble a CR2032 button battery, and test the performance using the Xinwei button battery all-in-one machine MIHW-200-160CH-B. The test temperature is 25°C, the battery operating voltage is 2.0V to 4.8V, and the test method is constant current charge and discharge mode. The battery is first cycled 3 times at a rate of 0.1C, and then cycled 300 times at a rate of 1C.

[0066] Test results see Figure 6 and Table 1.

[0067] Table 1

[0068]

[0069] From Table 1 and Figure 6 From the results, it can be seen that the positive electrode material after the nickel cobalt manganese oxide particles are coated with a layered / spinel composite phase transition layer and a lithium zirconium phosphate layer in sequence has a higher first discharge capacity at 0.1C than the uncoated nickel cobalt manganese oxide positive electrode material, and the capacity retention rate after 300 cycles and the first coulomb efficiency are better than the uncoated control example. The coated material cycles 300 times at 1C, and the capacity retention rate is greater than 77%. With the increase of the coating amount of lithium zirconium phosphate, the capacity retention rate after 300 cycles at 1C shows a trend of first increasing and then decreasing, wherein a coating amount of 0.5-3% is preferred, and 0.5-2% is more preferred, with the best being achieved at a coating amount of 1%. This shows that lithium zirconium phosphate, as a coating layer for lithium nickel cobalt manganese oxide, can improve the specific capacity and cycle performance of the material.

[0070] The button batteries assembled in Example 1 and the comparative example were tested using the MIHW-200-160CH-B button battery integrated machine. The test method was constant current charge and discharge, the rate was 1C, the number of cycles was 300, and the median voltage and the number of cycles were recorded. The test results are shown in Figure 7 .

[0071] from Figure 7 It can be seen that the average voltage attenuation of the positive electrode material in Example 1 is 218 mV / 100 cycles, 365 mV / 200 cycles, and 440 mV / 300 cycles, which are significantly lower than 431 mV / 100 cycles, 595 mV / 200 cycles, and 647 mV / 300 cycles of the comparative example.

[0072] From the above results, it can be concluded that the positive electrode material of the present invention is composed of a core of lithium nickel cobalt manganese oxide particles, a layered / spinel composite phase transition layer formed in the subsurface layer, and a lithium zirconium phosphate surface layer, wherein the lithium zirconium phosphate coating layer is a surface-grain boundary integrated modification layer, which can achieve complete coating of the material surface and bulk phase. The lithium zirconium phosphate surface layer can increase the surface oxygen saturation, inhibit oxygen precipitation under high voltage, and improve the structural stability of the material, while the spinel phase in the transition layer has a three-dimensional lithium ion channel and high mechanical strength, which can improve the transmission efficiency of lithium ions, and ultimately make the material have good electrochemical properties.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A lithium-rich manganese-based positive electrode material, characterized in that: It comprises a lithium nickel cobalt manganese oxide core, a layered / spinel composite phase transition layer coated on the surface of the core, and a lithium zirconium phosphate layer coated on the surface of the layered / spinel composite phase transition layer; The chemical formula of the lithium nickel cobalt manganese oxide core is shown in formula (I): aLi2MnO3·(1-a)LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2(I); Among them, 0.4<a<0.6; The chemical formula of the lithium zirconium phosphate is shown in formula (II): LiZr2(PO4)3(II); The chemical formula of the layered / spinel composite phase transition layer is shown in formula (III): aLi2MnO3·(1-a)LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2·LiMn2O4(III)。 2. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The inner core of the lithium nickel cobalt manganese oxide is a quasi-spherical particle with an average particle size of 5 to 100 μm, the thickness of the transition layer is 0.5 to 5.0 nm, and the thickness of the lithium zirconium phosphate layer is 0.1 to 2.0 nm.

3. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The average particle size of the lithium nickel manganese cobalt oxide core is 5 to 50 μm, the thickness of the transition layer is 0.5 to 5.0 nm, and the thickness of the lithium zirconium phosphate layer is 0.1 to 2.0 nm.

4. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The weight percentage of the lithium zirconium phosphate is 0.5-5% relative to the weight of the lithium nickel cobalt manganese oxide core.

5. The method for preparing a lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Obtaining lithium nickel cobalt manganese oxide particles; S2. The lithium nickel cobalt manganese oxide particles, lithium source, zirconium source, phosphorus source and flux are uniformly mixed, sintered at 300-500°C for 0.5-2h, and then cooled to room temperature, and the product is washed, filtered, and the residue is dried; S3. Annealing the dried filter residue to obtain the lithium-rich manganese-based positive electrode material.

6. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: In S2, the mixing is: uniformly mixing the lithium nickel cobalt manganese oxide particles, lithium source, zirconium source, phosphorus source and flux in a solvent, and removing the solvent; preferably, in S2, the mixing is: uniformly mixing the lithium source, zirconium source and phosphorus source in an organic solvent to obtain slurry I, mixing the flux in water to a paste to obtain slurry II, uniformly mixing the lithium nickel cobalt manganese oxide particles, slurry I and slurry II, and drying to remove the organic solvent and water; more preferably, the organic solvent is a mixture of one or more of alcohols, aromatic hydrocarbons, ethers and ketones.

7. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The lithium source is at least one of lithium hydroxide, lithium nitrate, lithium sulfate, lithium chloride, lithium oxalate, lithium phosphate, lithium hydrogen phosphate and lithium carbonate; the zirconium source is at least one of zirconium nitrate, zirconium sulfate, zirconium chloride and hydrates thereof; the phosphorus source is at least one of (NH4)2HPO4, NH4H2PO4, lithium phosphate and lithium dihydrogen phosphate; the flux is at least one of LiCl, KCl, NaCl and CaCl2.

8. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: The flux includes a first flux and a second flux; the first flux is at least one of LiCl and CaCl2; the second flux is at least one of KCl and NaCl; preferably, the flux is a mixture of LiCl and KCl; more preferably, the eutectic temperature of LiCl and KCl after mixing in proportion is 353°C.

9. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: In S3, the annealing treatment is performed at a temperature of 180-250°C and for a time of 45-120 minutes.

10. A lithium ion battery, characterized in that: The invention comprises: a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the lithium-rich manganese-based positive electrode material as described in any one of claims 1 to 4, or the lithium-rich manganese-based positive electrode material prepared by the method as described in any one of claims 5 to 9.